Validation of the Sasang Personality Questionnaire in high school students - Soo Jin Lee; Sang Yun Han; Yong-Jae Lee; You-Sun Ko; Nayoung Bae; Jinhong Cheon; Han Chae (Integrative Medicine Research)
Background: The Sasang Personality Questionnaire (SPQ) is an objective measure of Yin–Yang temperament of Sasang typology with proven clinical and structural validity; however, it has not been validated in people younger than 20 years. The purpose of this study was to examine the biopsychological structure of the SPQ in high school students. Methods: A total of 670 Korean high school students (365 boys and 305 girls) completed the SPQ, Junior version of Temperament and Character Inventory (JTCI), and weight and height measures. The correlation between the SPQ and JTCI subscales was investigated, and the differences of these subscales, body mass index, and Pondera Index between the high (30%), middle (40%), and low (30%) SPQ total score groups were examined with analysis of variance. The profile analysis was also performed to compare JTCI subscale profiles of the three SPQ total score groups. Results: The SPQ total score significantly correlated positively with JTCI novelty seeking (r = 0.548 and r = 0.540) and negatively with JTCI harm avoidance (r = –0.393 and r = –0.395) in boys and girls, respectively. The JTCI novelty-seeking score is significantly higher in the high SPQ total score group (24.12 ± 5.27 and 24.15 ± 5.17 for boys and girls, respectively) than in the low SPQ total score group (16.49 ± 5.08 and 17.24 ± 4.83, respectively), and the JTCI harm-avoidance score is significantly higher in the low SPQ total score group (25.34 ± 6.08 and 26.64 ± 5.77 for boys and girls, respectively) than in the high SPQ total score group (19.27 ± 6.62 and 19.23 ± 6.00, respectively). The JTCI subscale profiles for the three SPQ total score groups were significantly different for boys (degrees of freedom = 3.416, F = 292.16, p < 0.001) and girls (degrees of freedom = 3.4, F = 230.51, p < 0.001). There were no significant correlations or differences in body mass index and Pondera Index among the SPQ total score groups. Conclusion: The results showed that the biopsychological structure of the SPQ in adolescents is robust, similar to that in the adult population. The SPQ might be useful for the application of Sasang typology in pediatrics.